E eu, que já fui uma brasa, se assoprarem posso acender de novo : arqueologia enquanto evento na trajetória de duas pioneiras - Santos, Tatiana de Lima Pedrosa (2012)
The thesis presents a discursive approach from the perspective of two Schools of Theoretical and Methodological Brazilian Archaeology. Highlighting about two exponents in Brazilian Archaeology: Annette Laming-Emperaire and Betty Jane Meggers. The discursive analysis outlined here is based on the interpretation theory of Paul Ricoeur and investigates how the transformation of these two archeologists in Events in Brazilian Archaeology was: the French School and the American School. Based on the tripartite dynamic from relationship text-reader context, the discourse referenced here comes the dialectic Event - Meaning, since from the pioneering of theses researchers.